Opportunities of Atomic Layer Deposition for Perovskite Solar Cells. (10th September 2015) - Zardetto, Valerio; Di Giacomo, Francesco; Mohammed, Mahir Asif; Lucarelli, Giulia; Razza, Stefano; D'Epifanio, Alessandra; Licoccia, Silvia; Kessels, W.M.M.; Di Carlo, Aldo; Brown, Thomas M.; Creatore, Mariadriana
Abstract : The fabrication of different functional layers by means of atomic layer deposition is proposed for the novel organo-lead halide perovskite solar cells. A plasma- assisted process at 150 °C was adopted to deposit an efficient TiO2 compact blocking layer on ITO-polymer substrates. Efficient flexible devices were obtained already with layers as thin as 10 nm. A Thermal ALD Al2 O3 process at 150 °C was successfully applied on a mesoscopic anatase TiO2 structure: an improvement of the overall performance of the solar cell (+13%) was measured with only 1 ALD cycle compared to devices without over-layer. Interestingly, a drastic reduction of the performance was observed when increasing the number of the cycles